SOFTWARE IS AN ABSTRACT ARTIFACT. - IRMAK, Nurbay (Grazer Philosophische Studien, 2013)
Software is a ubiquitous artifact, yet not much has been done to understand its ontological nature. Th ere are a few accounts offered so far about the nature of software. I argue that none of those accounts give a plausible picture of the nature of software. I draw attention to the striking similarities between software and musical works. Th ese similarities motivate to look more closely on the discussions regarding the nature of the musical works. With the lessons drawn from the ontology of musical works I offer a novel account of the nature of software. In this account, software is an abstract artifact. I elaborate the conditions under which software comes into existence; how it persists; how and on which entities its existence depends.